1995
DOI: 10.1210/endo.136.7.7789342
|View full text |Cite
|
Sign up to set email alerts
|

The thyrotropin (TSH) receptor transmembrane domain mutation (Pro556-Leu) in the hypothyroid hyt/hyt mouse results in plasma membrane targeting but defective TSH binding.

Abstract: The hyt/hyt mouse is hypothyroid because of a mutation in the TSH receptor (TSH-R). In this report, we confirm the presence of a Pro to Leu mutation in amino acid 556 of the fourth transmembrane domain (TM4) of the TSH-R. This Pro is highly conserved in members of the G protein-coupled seven-transmembrane family of receptors. Insertion of this mutation into the wild-type rat receptor eliminated TSH binding and receptor function in transfected 293 and COS cells. Wild-type TSH-R conferred a 7.4-fold increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…Mice homozygous for the mutation have a normally located but hypoplastic and poorly functioning thyroid (Beamer et al 1981, Stein et al 1994, Gu et al 1995. In western blot experiments, Tshr hyt/hyt thyroids exhibited one wide immunoreactive band corresponding to protein(s) of approximately 150 kDa molecular mass ( Fig.…”
Section: Onset Of Duox Protein Expression During Mouse Thyroid Embryomentioning
confidence: 98%
“…Mice homozygous for the mutation have a normally located but hypoplastic and poorly functioning thyroid (Beamer et al 1981, Stein et al 1994, Gu et al 1995. In western blot experiments, Tshr hyt/hyt thyroids exhibited one wide immunoreactive band corresponding to protein(s) of approximately 150 kDa molecular mass ( Fig.…”
Section: Onset Of Duox Protein Expression During Mouse Thyroid Embryomentioning
confidence: 98%
“…Testing a hypomorphic strain for Tshr revealed that this gene does indeed have a strong effect on both TG and HDL levels. The mutant Tshr hyt strain has a Pro556Leu mutation (19,20) that makes it hypothyroid with decreased TG and increased HDL relative to controls. In our QTL, D2 alleles give rise to both increased TG and increased HDL, so the effect is not quite the same.…”
Section: Chr12@45 CM (Tgq23) Candidate Genementioning
confidence: 99%
“…Animal protocols were reviewed and approved by the Animal Care and Use Committee at The Jackson Laboratory. Tshr hyt was originally identified as a spontaneous hypothyroid mutation in an RF/J mouse and was subsequently backcrossed into a BALB/cByJ background (N 10 ) and maintained through heterozygous 3 wild-type sib mating, because homozygotes are infertile (19,20). A strain deficient in villin1 (Vil1), a protein expressed in the brush border of the intestine, was generated at the Institut Curie (21) by villin1 gene targeting in 129S2/SvPas ES cells followed by injection into C57BL6 blastocysts; chimeric mice were subsequently intercrossed with DBA/2 mice to generate homozygous Vil1 2/2 mice on a mixed 129S2, B6, and D2 background.…”
mentioning
confidence: 99%
“…The hyt/hyt thyroid is a very small bi-lobed gland situated in the normal position [1,22]. The causal gene of hypothyroidism has been identified as Tg in cog/cog [11] and the TSH receptor [8] in hyt/hyt.…”
Section: Figmentioning
confidence: 99%